Prognostic role of preoperative De Ritis ratio in upper tract urothelial carcinoma treated with nephroureterectomy - Mori, Keiichiro; Janisch, Florian; Mostafaei, Hadi; Kimura, Shoji; Lysenko, Ivan; Karakiewicz, Pierre I; Briganti, Alberto; Enikeev, Dmitry V; Rouprêt, Morgan; Margulis, Vitaly; Chlosta, Piotr; Nyirady, Peter; et al. (Urologic oncology, 2020)
PURPOSE: To validate the predictive and prognostic role of the De Ritis ratio in patients with upper tract urothelial carcinoma (UTUC) treated with radical nephroureterectomy in a large multi-institutional cohort. MATERIALS AND METHODS: The preoperative De Ritis ratio was assessed in a multi-institutional cohort of 2,492 patients. An altered De Ritis ratio was defined as a ratio >1.35. Logistic regression analyses were performed to assess the association of the De Ritis ratio with advanced disease. The association of the De Ritis ratio with survival outcomes was evaluated using Cox proportional hazards regression models. RESULTS: An altered De Ritis ratio was observed in 985 (41.5%) patients; it was associated with a more advanced pathological features. In a preoperative model, the De Ritis ratio was an independent predictive factor for the presence of lymph node metastasis and muscle-invasive and nonorgan-confined disease (P < 0.05). Compared to patients with a normal De Ritis ratio, those with an altered De Ritis ratio had worse recurrence free (P <0.0001), cancer specific (P = 0.0003), and overall survival (P = 0.0014) in the Kaplan-Meier analyses. In the multivariable analyses that was adjusted for the effects of standard clinicopathologic features, the De Ritis ratio did not retain its independent prognostic value. CONCLUSIONS: In UTUC, the preoperative De Ritis ratio is associated with adverse clinicopathologic features and independently predicts features of biologically and clinically aggressive UTUC. Therefore, it might be useful to incorporate the De Ritis ratio into prognostic tools in selecting appropriate treatment strategies.
Keywords: nádory močovodu; Lymph node metastasis; nádory ledvin; Upper tract urothelial carcinoma; Male; retrospektivní studie; Survival Rate; karcinom z přechodných buněk; předoperační období; prognóza; Kidney Neoplasms; Aged; mužské pohlaví; senioři; De Ritis ratio; Alanine Transaminase; Nephroureterectomy; Ureteral Neoplasms; Aspartate Aminotransferases; alanintransaminasa; lidé; ženské pohlaví; Humans; Prognosis; nefroureterektomie; Preoperative Period; Retrospective Studies; aspartátaminotransferasy; Female; Nonorgan-confined disease; Carcinoma, Transitional Cell; míra přežití